Application of Evolutionary Algorithms for Harmonic Profile Optimization in Symmetric Multilevel Inverter used in Medical Electronic Equipments - Menaka, S.; Muralidharan, S. (Current Signal Transduction Therapy, 2019)
Background: Inverters are finding applications in electrical field where conversion from Direct Current (DC) to Alternate Current (AC) has become an inevitable option. The need of Multi Level Inverter (MLI) is to provide a high output power from medium voltage source. High power quality is the very basic important requirement for MLI used in medical electronic equipment. Harmonic elimination in MLI is a challenging one and is solved by optimum switching of power electronic switches present in the MLI topology. Methods: Several control strategies have been proposed for harmonic elimination in multilevel inverters. Newton-Raphson method is the conventional and iterative based method to obtain optimum switching angle to minimize the Total Harmonic Distortion (THD). But it requires an initial guess of switching angles which is very close to the exact solution. To overcome this, harmonic elimination is converted into an optimization task and is solved by using evolutionary algorithms such as Genetic Algorithms (GA) and Particle Swarm Optimization (PSO). GA and PSO offer optimum switching angles to minimize THD and used to increase the robustness of the system. Results: The performance of proposed symmetric 21 level multilevel inverter with GA and PSO techniques are analysed and the objective of minimum THD is obtained by using MATLABSIMULINK software.In experimental setup, FPGA controller has been used to generate the Pulse Width Modulation (PWM) control signals according to the proposed soft computing based switching strategy. The experimental result is used to verify the ability of the proposed system for the generation of desired output voltage with minimum THD. Conclusion: The proposed symmetric MLI with evolutionary algorithm based switching is a good choice for medical electronic equipment used in hospital to obtain quality power with minimum THD.
Keywords: medical electronic equipments